Editor's Note - Scott, Mark A. (Cistercian studies quarterly, 2014)
People whom the editor would like to thank for their contributions to the journal are mentioned which include associated editor Marsha Dutton, supportive proofreader Martha Krieg and book review editor Paul Andrew Tanner.m